Influence of Trust on Customer Loyalty in The Small and Medium Enterprises Sector in Tanzania - Hirji , Naheed; Kara, Nasra (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2024)
This paper examined the influence of trust on customer loyalty in SMEs in Tanzania. The study used trust-commitment theory, behaviourist theory, and cognitive theory to determine the influence of trust on customer loyalty in SMEs in Tanzania. Customers from bars, hair salons, and kiosks in Dodoma Urban City participated in the survey. Convenience sampling was used to obtain the sample size of 288 respondents. The study data was obtained from customers using questionnaires. The questionnaires were self-administered to customers of bars, hair salons, and kiosks to gather data. Descriptive statistics was used to summarize data and show meaningful patterns while inferential statistics which included correlation analysis and regression analysis was employed to test the study hypotheses. The findings showed that trust significantly influenced customer loyalty. The study therefore concludes that the application of trust improves customer loyalty in SMEs in Tanzania.